Direct oral anticoagulants (DOACs): From the laboratory point of view - Margetić Sandra; Goreta Sandra Šupraha; Ćelap Ivana; Razum Marija (Acta Pharmaceutica)
Direct oral anticoagulants (DOACs) represent a new generation of drugs that have been increasingly used in the prevention and treatment of thromboembolic states. According to the mechanism of anticoagulant action, DOACs are divided into two groups: direct inhibitors of thrombin (dabigatran) and direct inhibitors of activated factor X (FXa) (rivaroxaban, apixaban, edoxaban, betrixaban). Compared to the vitamin K antagonists, DOACs are superior in terms of onset of action, pharmacokinetic and pharmacodynamics properties and fixed daily dose without the need for routine coagulation monitoring. Despite these advantages, there are clinical conditions in which laboratory measurement of DOACs should be performed. Although DOACs have an impact on screening haemostasis assays (prothrombin time, PT; activated partial thromboplastin time, aPTT; and thrombin time, TT), these tests are not appropriate for quantifying drug levels. Therefore, specific quantitative methods (LC-MS/MS as a gold standard method for all DOACs, coagulometric and chromogenic assays for dabigatran, and chromogenic anti-Xa assays with drug-specific calibrators for inhibitors of FXa) should only be used for determination of DOACs concentration. The aim of this review is to present all aspects of laboratory assessment of DOACs, including pre-analytical, analytical and post-analytical factors in the overall testing process with a special accent on the available specific quantitative methods for measurement of DOACs in circulation.